Radiofrequency Ablation of Pancreatic Cancer - Sarno, Alessandro; Beleù, Alessandro; De Robertis, Riccardo; Giannotti, Gabriele; Tedesco, Giorgia; Paiella, Salvatore; D'Onofrio, Mirko (Digestive Disease Interventions, 2019)
Radiofrequency ablation (RFA) is emerging as a safe and feasible technique to treat various pancreatic lesions. In particular, pancreatic ductal adenocarcinoma (PDAC) is the most frequent treated lesion. Nowadays, PDAC treatment by means of RFA is limited to locally advanced, non-resectable, but non-metastatic lesions. The aim of this article is to describe the RFA technique, its results and possible complications.
Keywords: pancreas; radiofrequency ablation; pancreatic adenocarcinoma